Medicinal Plant Compounds for Combating the Multi-drug Resistant Pathogenic Bacteria: A Review - Mulat, Mulugeta; Pandita, Archana; Khan, Fazlurrahman (Current Pharmaceutical Biotechnology, 2019)
Background: Globally, people utilize plants as the main source of remedy to heal various ailments. Medicinal plants have been utilized to treat ailments since the invention of modern scientific systems of medicine. The common remedy of infectious diseases mainly depends on the inhibition capacity of compounds or killing potential. The issue may give a clue for the development of a novel antimicrobial agent. Methods: Currently, microorganisms which are resistant towards antibiotics are probably a matter of serious concern for the overall well-being of health. At the moment, new therapeutic targets aside from the microorganism wall-based activities are in progress. For instance, the autoinducer molecules produced by the quorum sensing system are used to control antibiotic resistance and biofilm formation. Results: This therapeutic target is well-studied worldwide, however, the scientific data are not updated and only current studies started to gain insight into its perspective as a target to struggle against infectious diseases. Microbial resistance against antimicrobial compounds is a topic of serious concern in recent time. Conclusion: Hence, this paper aims to confer a current overview of the novel compounds, quorum sensing, quorum quenching, biofilm formation in the development of antibiotic resistance and an update on their importance as a potential target for natural substances.
Keywords: Antibiotics